Get Shown the Light: Improvisation and Transcendence in the Music of the Grateful Dead - Kaler, Michael (Studies in the Grateful Dead, 2023)
Michael Kaler demonstrates that the Grateful Dead developed a radical new way of playing rock music as a means to unleashing the spiritual and transformative potential of their music